2019
DOI: 10.7554/elife.50566
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of an interneuron response depends on an integrated sensory state

Abstract: The central nervous system transforms sensory information into representations that are salient to the animal. Here we define the logic of this transformation in a Caenorhabditis elegans integrating interneuron. AIA interneurons receive input from multiple chemosensory neurons that detect attractive odors. We show that reliable AIA responses require the coincidence of two sensory inputs: activation of AWA olfactory neurons that are activated by attractive odors, and inhibition of one or more chemosensory neuro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 57 publications
(104 reference statements)
2
39
0
Order By: Relevance
“…Because ASK activation promotes reversals ( Wakabayashi et al 2004 ; Gray et al 2005 ), suppression of calcium signaling by a chemoattractant and activation by a chemorepellent could both contribute to appropriate behavioral responses and locomotion strategies in complex chemosensory environments. For example, calcium imaging revealed that inhibition of ASK by the addition of diacetyl contributes to the disinhibition of the downstream interneuron AIA, allowing AIA to more reliably respond to diacetyl-evoked depolarization of AWA ( Dobosiewicz et al 2019 ). While the application of E. coli supernatant decreases ASK calcium levels, an elevation (OFF response) was seen upon its removal ( Zaslaver et al 2015 ).…”
Section: Neurons and Their Contributions To Chemosensationmentioning
confidence: 99%
See 3 more Smart Citations
“…Because ASK activation promotes reversals ( Wakabayashi et al 2004 ; Gray et al 2005 ), suppression of calcium signaling by a chemoattractant and activation by a chemorepellent could both contribute to appropriate behavioral responses and locomotion strategies in complex chemosensory environments. For example, calcium imaging revealed that inhibition of ASK by the addition of diacetyl contributes to the disinhibition of the downstream interneuron AIA, allowing AIA to more reliably respond to diacetyl-evoked depolarization of AWA ( Dobosiewicz et al 2019 ). While the application of E. coli supernatant decreases ASK calcium levels, an elevation (OFF response) was seen upon its removal ( Zaslaver et al 2015 ).…”
Section: Neurons and Their Contributions To Chemosensationmentioning
confidence: 99%
“…The AWA olfactory neuron pair senses bacterially produced volatile cues to direct animals toward potential food sources ( Bargmann et al 1993 ; Larsch et al 2013 ; Choi et al 2016 ; Worthy et al 2018a ; Dobosiewicz et al 2019 ; Table 1 ). However, there are sex differences in attraction to some odorants, including diacetyl ( Lee and Portman 2007 ; White et al 2007 ; Ryan et al 2014 ; Barr et al 2018 ).…”
Section: Neurons and Their Contributions To Chemosensationmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified two interneurons, AIA and RIA, whose activity was modulated in a stimulusand valence-specific manner, both following short-and long-term learning. The AIA interneurons are postsynaptic to most of the chemosensory neurons (White et al , 1986;Cook et al , 2019) , and had been shown to integrate various chemosensory inputs (Shinkai et al , 2011;Larsch et al , 2015;Dobosiewicz, Liu and Bargmann, 2019) . While AIA activity promotes forward locomotion (Garrity et al , 2010) , we found that long-term aversive training increased AIA activity together with increase in reversal rates (Fig.…”
Section: Discussionmentioning
confidence: 99%